Self-Organization of Student Youth under Conditions of Social Uncertainty - Hoian , Ihor; Yakovleva , Svitlana; Hulias , Inesa; Fomina , Iryna (Insight: the psychological dimensions of society, 2024)
The aim is a theoretical and empirical research of the psychological characteristics and types of self-organization among student youth in conditions of social uncertainty. Methods. The sample consisted of students from three levels of higher education who were studying at universities in Ukraine, a total of 362 individuals (M = 22.86; SD = ±2.84). An important criterion that united the subjects is that, during the martial law all of them found themselves in a difficult social situation, and their living and studying underwent significant spatiotemporal and content changes. Psychodiagnostic methods that were validated by psychologists on Ukrainian samples were used. The main dimensions of readiness for change, self-organization, and self-regulation were determined by: “Readiness to Change Questionnaire” (RCQ) (Rollnick et al., 1992); “Self-Organization of Activity Test-Questionnaire” (SOATQ) (Mandrikova, 2010); and the questionnaire “Style of Behavior Self-Regulation” (SBSR) (Morosanova, 1991). Results. Twenty-five statistically significant correlations (p < .050; p < .010; p < .001) were identified, demonstrating regular dependencies among the researched parameters. Through cluster analysis using the k-means method, four types of self-organization among student youth in conditions of social uncertainty were established: “Adventurous self-organization” (AS) (Cluster 1, n = 47; 12.98%); “Optimistic self-organization” (OS) (Cluster 2, n = 143; 39.50%); “Passionate self-organization” (PS) (Cluster 3, n = 97; 26.80%) and “Tolerant self-organization” (TS) (Cluster 4, n = 75; 20.72%). Discussion and conclusions. It was substantiated that “adventurousness”, which has the strongest direct correlation with “purposefulness” (R = .231; p < .001), is dangerous. It is explained that a high level of purposefulness and constructive ambition, which is characteristic of student organization leaders, definitely borders on adventurousness, with youthful maximalism and can bring record results and feats, as well as have reverse consequences and deep disappointments. It is substantiated that “AS” and “PS” are destructive, while “OS” and “TS” are constructive types of self-organization. It is summarized that the outlined types represent a successful attempt at clustering the empirical data with the aim to discover new knowledge. It is recommended that the obtained results be implemented in the structural units of higher education institutions that work with student youth.
Keywords: self-organization, motivation, resilience, values, gender, inclusive educational environment, self-actualization.